The Management of Peritumoral Brain - Bisri, Dewi Yulianti; Bisri, Tatang (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Brain edema is classified into four main types: vasogenic, cellular, osmotic, and interstitial. These types may be triggered by various conditions, such as head injuries, vascular ischemia, intracranial lesions, and obstructive hydrocephalus. Several factors are associated with the development of (the swelling of the brain including tumors, physical injuries, insufficient oxygen supply (hypoxia), infections, disruption in metabolism, or acute hypertension. Vasogenic brain edema, the most prevalent form of brain edema, is characterized by a blood- brain barrier (BBB) disorder. When the BBB is compromised, ions and proteins move more easily into the extravascular space, creating an osmotic effect that fluid into the brain’s interstitium. In brain tumors, cerebral edema occurs due to leakage of plasma into the parenchyma caused by impaired function of cerebral capillaries. Management of brain edema focuses on two key strategies: preventing further damage caused by the increased fluid in the brain, and addressing the underlying cause of the edema. Corticosteroids are frequently used as a primary therapy for this condition. While low-dose corticosteroids are preferred to minimize serious adverse effects such as myopathy or diabetes, higher doses of dexamethasone-sometimes along with osmotherapy (e.g. mannitol) or surgical interventions- may be necessary in emergency situations. Careful tapering of corticosteroids is essential to prevent dependence or withdrawal symptoms. New therapies, such as vascular endothelial growth factor receptor inhibitors and corticotropin-releasing factor, require additional clinical evaluation. A thorough understanding of pathophysiology of brain edema is crucial for optimizing the treatment strategies both before and after surgical procedures.